In-field dependences of the critical current density Jc in GdBa2Cu3O7-d coated conductors produced by Zr irradiation and post-annealing at low temperatures - Haberkorn, N.; Suárez, S.; Lee, Jae-Hun; Moon, S. H.; Lee, Hunju; Puig, Joaquín; Haberkorn, Néstor (Elsevier, 2019)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina